(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Family caregivers of persons with bipolar disorder and schizophrenia experience high level of burden and compromised quality of life. A considerable amount of burden on the caregivers often leads to display of certain attitudes towards persons with severe mental illness called expressed emotion, which then leads to poor quality of patients as well. Although numerous studies dealing with these issues separately are present, but studies dealing with relationship, using mixed methodology, among these issues are scarce. Adherence to a drug regime is a significant issue in the clinical management of schizophrenia. A study of adherence in bipolar disorder showed that slightly more than one-half of the patients studied were fully adherent, 20% were partially adherent, and nearly 30% were non-adherent. Risk factors for non-adherence in this group included younger age, minority status, substance abuse, and homelessness (Shehu, et al., 2019). This study assessed and Analysis on the predictors of good knowledge of medication Adherence among care- givers of patients with Schizophrenia in some selected Hospital of Jigawa State, Nigeria. A quasi-experimental psycho-educational intervention study was conducted with before and after design among care givers of patients with Schizophrenia in some selected hospitals of Jigawa State, Nigeria. The study population comprised all the eligible care- givers of patients with schizophrenia within the study area, who were selected and agreed to participate in the study. A sample size of one hundred and thirty participants each for both the experimental and control groups were selected using a multistage sampling technique. Data was collected using Questionnaire Data collected was coded, entered, and analyzed using the Statistical Package for the Social Sciences (SPSS) version 22. After adjusting for the confounding effects using logistic regression analysis; type of treatment (ECT) was found to be negative predictors of good knowledge on medication adherence to treatment among study participants (AOR=0.50, 95%CI=0.27 – 0.85). While, cost of treatment of more than one thousand five hundred naira per day (AOR=2.5, 95%CI=2.11 – 8.33), combination of drugs and ECT (AOR=3.01, 95%CI=1.85 – 14.76), presence of side effects (AOR=4.00, 95%CI=2.05-21.55) and monthly income (AOR=3.00, 95%CI=1.01-15.88) were positive predictors of good knowledge on medication adherence among the study participants in the experimental groupSocial support had a significant correlation with caregivers’ QoL. Caregivers should be encouraged to request assistance from other family members and friends in providing care, especially when caregivers are unemployed or long-time carers. Mental health education campaigns and helping families to maintain and enhance a supportive social network may provide useful means to improve caregivers.